O Ministério Público estadual e a justiciabilidade do direito à qualidade do ensino fundamental público no Brasil: funções e interpretações - Cabral, Karina Melissa [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study is linked to the line of research Public Policy, School Organization and Teacher Education and had at investigating the role of the state prosecutor in the justiciability of the quality of public elementary school, proposing a reflection on the possibility of representatives of this body requires it legally through the Public Civil Action. As a proposal for quality measurement presents the discussion of the qualitative dimensions of education (inputs, processes and outcomes) in order to enable greater legal feasibility to requests for claiming the quality of basic education. During the research it was found that the MP composition there are also some subsidiary bodies of the functional activity are the Operational Support Centers - CAO's which function to aid the provision of services, information and monitoramente of government actions and policies public involving children and adolescents referring technical and legal information so that prosecutors can act in relation to these rights. The survey was conducted by mapping the actions of the organs of the State Prosecutor in the Brazilian states, focusing on the Centers for Operational Support Defense Education (CAODE) or the Centers for Children and Youth Operational Support (CAOIJ) that through use of the comparative method, coupled with the deepening of bibliographical and documentary research, analyzed the information obtained about the modus operandi of these bodies in actions involving claims that have as basis the dimensions of quality of basic education...

O presente estudo vincula-se à linha de pesquisa de Políticas Públicas, Organização Escolar e Formação de Professores e teve como objeto de investigação o papel do Ministério Público estadual na justiciabilidade da qualidade do ensino fundamental público, propondo uma reflexão sobre a possibilidade dos representantes deste órgão exigi-la juridicamente por meio da Ação Civil Pública. Como proposta para mensuração da qualidade apresenta-se a discussão das dimensões qualitativas da educação (insumos, processos e resultados) com o intuito de possibilitar uma maior viabilidade jurídica aos pedidos de exigibilidade da qualidade do ensino fundamental. Durante a pesquisa verificou-se que na composição do MP existem também alguns órgãos auxiliares da atividade funcional que são os Centros de Apoio Operacional - CAO ‘s que têm como função o auxílio, a prestação de serviços, informações e monitoramente de ações governamentais e políticas públicas que envolvam crianças e adolescentes remetendo informações técnico-jurídicas para que os representantes do Ministério Público possam atuar em relação aos direitos destes. A pesquisa foi realizada através de um mapeamento das ações dos órgãos do Ministério Público Estadual nos Estados brasileiros, enfocando os Centros de Apoio Operacional de Defesa da Educação (CAODE) ou os Centros de Apoio Operacional da Infância e Juventude (CAOIJ) que por meio do uso do método comparativo, aliado ao aprofundamento na pesquisa bibliográfica e documental, analisou as informações obtidas sobre a forma de atuação destes órgãos em ações que envolviam pedidos que tenham como fundamento as dimensões da qualidade do ensino fundamental...
Keywords: Educação; Ensino fundamental; Politicas publicas; Escolas - Organização e administração; Professores - Formação; Education